Rediscovery of Nesomyrmex clavipilis Wheeler, 1910 (Hymenoptera: Formicidae) after more than a century, with the first description of its worker - Arredondo, Brandon S.; Santos-Neto, Esperidião Alves Dos; Guerrero, Roberto J.; Delabie, Jacques Hubert Charles (Zootaxa, 2026)
The ant genus Nesomyrmex Wheeler, 1910, is a species-rich lineage with a broad tropical and subtropical distribution; however, several of its Neotropical species remain poorly understood. Nesomyrmex clavipilis Wheeler, 1910, was described from a single gyne collected in Grenada and has not been recorded again, leading to speculation about its possible local extinction. Recent fieldwork has resulted in the collection of new material of N. clavipilis. This included gynes and workers from multiple localities, allowing for the first reliable association of castes. Based on this material, we redescribe the gyne, representing the rediscovery of N. clavipilis 116 years after its original description, and provide the first description of the worker caste, accompanied by high-resolution images. We document intraspecific morphological variation, refine diagnostic characters, and present new data on the geographic distribution and natural history of the species. We also describe a previously unnamed sculptural feature, herein termed the rosette fovea, documented by scanning electron microscopy. New records extend the known distribution of the species to Brazil, Colombia, French Guiana, Paraguay, and Peru, and provide the first natural history data for the species. These findings contribute to a more accurate understanding of species boundaries within Nesomyrmex and highlight the importance of renewed sampling efforts for resolving taxonomic gaps in Neotropical ant faunas.